Analisis Pengaruh Covid-19 Terhadap Kinerja Keuangan Lippo Group Yang Terdaftar Di BEI Tahun 2018-2021 - Emi Susanti Purba; Devi Ruminta Nainggolan; Roini Nela Setia Manurung; Tina Novianti Sitanggang; Renika Hasibuan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study was conducted to..see whether Covid-19 had an influence on the Financial Performance of Lippo Groupsubsidiaries which on the Indonesia Stock Exchange in 2018-2021 through the variables determined in..this study. Datafrom financial reports every year, has carried out the process of determining the sample with adjusted criteria. The population is Lippo Group subsidiaries, using purposive sampling method, the final sample is 15 companies. This research aims to provide knowledge and become a source of information to help futre researchers, students,companies and external parties who need information. According to the output of this..study , it is partially known..that..there is a significant.influence of Current Ratio on financial performance. Return..On Assets, Working Capital turnover, Return..On Equity do..not have a significant..effect on Financial Performance. But all variables in..thisstudy ensure that..there..is a have a simultaneously effect on Financial Performance.